A grape-like N-doped carbon/CuO-Fe2O3 nanocomposite as a highly active heterogeneous Fenton-like catalyst in methylene blue degradation. (10th December 2019) - Ren, Bin; Miao, Junfeng; Xu, Yuelong; Zhai, Zuozhao; Dong, Xiaoxi; Wang, Shasha; Zhang, Lihui; Liu, Zhenfa
Abstract: An N-doped carbon/CuO-Fe2 O3 (NC-CuFe) nanocomposite was successfully prepared via a simple, green one-pot annealing method. Different techniques were employed to characterize the physical and chemical properties of the prepared products, such as the composition, texture, structure and reducibility. XRD, XPS, TPR and especially TEM demonstrated the formation of CuFe2 O4 in the Cu-doped composite. All the Cu-doped materials (NC-CuFe) showed higher activity in the Fenton reaction of MB degradation than the non-doped sample (C-Fe). In particular, the composite doped with 10 wt% CuO (NC-CuFe-2) exhibited the best performance, with approximately 98% of the methylene blue (MB) removed in 180 min in the presence of H2 O2 . The high specific surface area, the mutual charge interaction between Cu 2+ and Fe 3+, the mobility of the lattice oxygen and the high pyridinic N content in NC-CuFe-2 were responsible for the high activity in the Fenton reaction. Moreover, NC-CuFe-2 also demonstrated excellent stability and reusability, which were crucial for practical applications. Graphical abstract: Schematic illustration of the fabrication process of NC-CuFe-2 and Fenton-reaction for MB degradation. Image 1 Highlights: The novel N-doped carbon/CuO-Fe2 O3 were fabricated by one-pot annealing method. The novel N-doped carbon/CuO-Fe2 O3 exhibited an grape-like structure. The N-doped carbon/CuO-Fe2 O3 display good catalytic performance and reusability.